Efektivitas Pelaksanaan Program Magang Pembelajaran terhadap Kemampuan TPACK (Technological Pedagogical Content Knowledge) Mahasiswa Calon Guru Biologi FKIP Universitas Muhammadiyah Purwokerto - Mufida Nofiani; Teguh Julianto (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
The aim of research is analyse the efectivity of apprenticeship program towards TPACK   (Technological Pedagogical Content Knowledge) in biology prospective teacher. This research is descriptive with respondens are prospective teacher students in Biologi Education Department in University Muhammadiyah of Purwokerto. Data colection are obtained by questionnaire, observation, and interview. Validity of data is done with triangulation. The  questionnaire data indicates that students have technology knowledge amount 58%, content knowledge 76,22% (baik), pedagogical knowledge amount 73,67 % , pedagogical content knowledge amount 72, 27% , technological pedagogical knowledge amount 66,27%, and technological pedagogical content knowledge amount 66,93%.  Observation dan interview data is not much different with questionnaire. Finally  apprenticeship program is quite effective to give effect towards TPACK   (technological pedagogical content knowledge) in biology prospective teacher.